ANALYSIS OF DIGITAL MARKETING STRATEGIES (TIKTOK) FOR THE QOQOM DIMSUM WHOLESALE UMKM IN TANJUNG MULIA HILIR URBAN VILLAGE, MEDAN CITY - Dinda Aulia; Teguh Dwi Putra; Ngatno Sahputra (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze digital marketing via TikTok for the UMKM “Grosir Dimsum Qoqom” in Tanjung Mulia Hilir Subdistrict, Medan City, covering content strategies, the impact on sales, and the challenges encountered. A qualitative descriptive research method was employed, utilizing data collection techniques such as observation, interviews, and documentation. The study’s informants included the business owner, production staff, and customers. The results indicate that TikTok is utilized through the periodic uploading of content featuring product videos, production processes, price promotions, and ordering information. The use of hashtags, trending music, and comment interactions has successfully expanded promotional reach and boosted consumer interest. TikTok also plays a role in building consumer trust by visually showcasing product quality. The impact of using TikTok is evident in increased engagement, an influx of new customers, and rising sales figures. However, the business faces challenges such as maintaining content creation consistency, limited human resources, algorithm changes, and intensifying competition. Based on a SWOT analysis, the digital marketing strategy via TikTok is considered effective for expanding the market and enhancing the competitiveness of the Dimsum Qoqom UMKM.